Impact of successful HCV treatment using direct acting antivirals on recurrence of well ablated hepatocellular carcinoma. Issue 2 (1st February 2022) - Elbaz, Tamer; Waked, Imam; El-Akel, Wafaa; Shaker, Mohamed Kamal; Abdelaziz, Ashraf Omar; Yousif, Monkez; El-Bendary, Mahmoud; Zaky, Samy; AbdAllah, Mohamed; Hassany, Mohamed; Esmat, Gamal; Doss, Wahid
ABSTRACT: Background: There are many contradictory studies that dealt with hepatocellular carcinoma (HCC) recurrence rate of well ablated hepatitis C virus (HCV) related HCC. We aim to assess the recurrence rate of previously ablated HCC in patients who received direct acting antiviral (DAA) for their HCV. Research design and methods: This is a retrospective data analysis of 523 HCV patients who have a history of successfully ablated HCC and eligible for HCV treatment. Retrieval was done to demographic/clinical data, HCV pretreatment investigations, HCV treatment outcome. Follow up for survival and HCC recurrence was done every 3 months using abdominal ultrasound and alfa-fetoprotein. Results: Mean age was 53.83 years. Sofosbuvir/daclatasvir/ribavirin was the most used regimen (35.4%) with 438 patients (83.7%) achieved sustained virologic response (SVR). The median duration for surveillance was 159 weeks. Hundred and five patients developed recurrent HCC, with a crude recurrence rate of 20.1%. There was no difference between HCV responders and non-responders in crude recurrence rate (p = 0.94) but HCC developed earlier in non-responders (p = <0.01). Conclusion: Recurrence of HCC remains a threat in HCV patients even after achieving an SVR. Implementation of long-term surveillance programs is highly recommended.